2016
DOI: 10.1007/s00394-016-1293-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns are associated with depressive symptoms among Chinese adults: a case–control study with propensity score matching

Abstract: The present study adds to the evidence that the sweets pattern and animal foods pattern are positively associated with the prevalence of high depressive symptoms. In contrast, the dietary pattern rich in vegetables, fruits, and soya bean products, but low in animal foods, candied fruits, cakes, ice cream, sugared beverages, and alcoholic drinks is negatively associated with the prevalence of high depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 50 publications
6
29
1
Order By: Relevance
“…An inverse association was also seen between adherences to the AHEI-2010 and depression, similar to civilian studies 25. Authors have demonstrated an association between a diet rich in fruits, vegetables, fish, whole grains and olive oil and moderate in red and processed meat with a reduction in depression symptoms 14 16 26.…”
Section: Discussionsupporting
confidence: 63%
“…An inverse association was also seen between adherences to the AHEI-2010 and depression, similar to civilian studies 25. Authors have demonstrated an association between a diet rich in fruits, vegetables, fish, whole grains and olive oil and moderate in red and processed meat with a reduction in depression symptoms 14 16 26.…”
Section: Discussionsupporting
confidence: 63%
“…Factors were named descriptively according to the food items showing high loading (absolute value) with respect to each dietary pattern as follows: “fruits and sweets” dietary pattern (factor 1), “healthy” pattern (factor 2) and “animal foods” pattern (factor 3). Similar dietary patterns were also observed in our previous study . For further analyses, factor scores were categorised into 4 equal groups by using quartile cut‐offs.…”
Section: Methodsmentioning
confidence: 56%
“…Dietary intake in the last month was assessed by a validated self‐administered food frequency questionnaire . The questionnaire comprised 81 food items, including 8 frequency categories ranging from “almost never drink” to “four or more cups per day” for beverages and 7 frequency categories ranging from “almost never eat” to “twice or more per day” for other foods.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary patterns have been previously implicated in the presence or development of depressive symptoms [14,15,36]. A case-control study conducted in Chinese adults found that a diet rich in fruits and vegetables was inversely associated with the prevalence of depressive symptoms [43]. Conversely, this study found that a diet that contains sweets (cakes, ice-cream, candied fruits, etc.)…”
Section: Introductionmentioning
confidence: 61%
“…Conversely, this study found that a diet that contains sweets (cakes, ice-cream, candied fruits, etc.) or animal products was positively associated with the prevalence of depressive symptoms [43]. Another study found that a diet with poor nutritional quality was associated with elevated depressive symptoms in young adult females [34].…”
Section: Introductionmentioning
confidence: 96%